2014
DOI: 10.1371/journal.pone.0086452
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit Estimates of Prey Consumption Reveal a New Krill Predator in the Southern Ocean

Abstract: Development in foraging behaviour and dietary intake of many vertebrates are age-structured. Differences in feeding ecology may correlate with ontogenetic shifts in dispersal patterns, and therefore affect foraging habitat and resource utilization. Such life-history traits have important implications in interpreting tropho-dynamic linkages. Stable isotope ratios in the whiskers of sub-yearling southern elephant seals (Mirounga leonina; n = 12) were used, in conjunction with satellite telemetry and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 126 publications
(225 reference statements)
3
34
1
Order By: Relevance
“…Vibrissae are often subsampled into 2 mm segments for isotopic analyses (e.g., Newland et al 2011;Walters et al 2014), and we therefore reported the average number of days represented by a 2 mm vibrissal segment to emphasize the temporal resolution of the biogeochemistry data obtainable from sequentially sampled vibrissae.…”
Section: Growth Rate Of Re-sampled Vibrissaementioning
confidence: 99%
See 4 more Smart Citations
“…Vibrissae are often subsampled into 2 mm segments for isotopic analyses (e.g., Newland et al 2011;Walters et al 2014), and we therefore reported the average number of days represented by a 2 mm vibrissal segment to emphasize the temporal resolution of the biogeochemistry data obtainable from sequentially sampled vibrissae.…”
Section: Growth Rate Of Re-sampled Vibrissaementioning
confidence: 99%
“…However, such a combined approach requires higher resolution SI data (Beltran et al 2015; also see Banks et al 2014). The SI signature captured along the length of keratinous tissue, such as feathers (Grecian et al 2015), nails, hair or vibrissae, provides a time-series of the species' dietary history, if analysed chronologically (Hückstädt et al 2012;Robertson et al 2012;Walters et al 2014;Beltran et al 2015). Numerous studies focussed on ascertaining the exact, species-and tissue-specific growth rates of slow-growing, biologically inert keratinous tissue of various species in different habitats (e.g., Greaves et al 2004;Rohwer et al 2009;Beltran et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations